Behaviour change techniques to change the postnatal eating and physical activity behaviours of women who are obese: a qualitative study. (5th November 2015) - Smith, DM; Taylor, W; Lavender, T
Abstract : Objective: To explore the experiences of postnatal women who are obese [body mass index (BMI) ≥ 30 kg/m 2 ] in relation to making behaviour changes and use of behaviour change techniques (BCTs). Design: Qualitative interview study. Setting: Greater Manchester, UK. Population or Sample: Women who were 1 year postnatal aged ≥18 years, who had an uncomplicated singleton pregnancy, and an antenatal booking BMI ≥ 30 kg/m 2 . Methods: Eighteen semi‐structured, audio‐recorded interviews were conducted by a research midwife with women who volunteered to be interviewed 1 year after taking part in a pilot randomised controlled trial. The six stages of thematic analysis were followed to understand the qualitative data. The Behavior Change Technique Taxonomy (version 1) was used to label the behaviour change techniques (BCTs) reported by women. Main outcome measures: Themes derived from 1‐year postnatal interview transcripts. Results: Two themes were evident: 1. A focused approach to postnatal weight management: women reported making specific changes to their eating and physical activity behaviours, and 2. Need for support : six BCTs were reported as helping women make changes to their eating and physical activity behaviours; three were reported more frequently than others: Self‐monitoring of behaviour (2.3), Prompts/cues (7.1) and Social support (unspecified; 3.1) . All of the BCTs required support from others for their delivery; food diaries were the most popular delivery method. Conclusion: Behaviour change techniques are useful to postnatal women who are obese, and have the potential to improve their physical and mental wellbeing. Midwives and obstetricians should be aware of such techniques, to encourage positive changes. Tweetable abstract: BCTs are useful to postnatal women who are obese, and have the potential to improve their wellbeing. Tweetable abstract: BCTs are useful to postnatal women who are obese, and have the potential to improve their wellbeing.